Dentists Attitude Towards Prevention in North-East Of Romania - Iulia Saveanu; Ioan Dănilă; Lucia Barlean; Carina Balcos (Romanian Society of Oral Rehabilitation, 2012)
The aim of this study was analyzed of attitudes and knowledge of the dentists of N-E region of Romanian country. Material and methods A questionnaire-based study was conducted including 152 dentists (72.4%-female, 27.6% males) aged between 25-65 years, from six areas of North-East Region, Romania. The questionnaire included 11 questions related to preventive practices in the dental office. Data were statistically analyzed using the SPSS14.00 program and chi-square test (p≤0.05). Results: The evaluation of the results was based on experience level in years: Gr. 1 = 0-5, Gr. 2 = 5-10, Gr. 3 = 10-20, Gr. 4 = more 20. Results The results shows that majority of the subject made primary prevention: local fluoridation 73% (111), oral hygiene 83.6% (127), sealants 73.7(112), scaling 89.5% (136) and only 25% (38) secondary prevention by restoration preventive with resins and most are in the Gr. 3 p≤0.05. Most practitioners know that they can influence both the risk of caries and periodontal disease Gr. 3 = 38.2% (58) and recommend a certain brush technique Gr.3=39.5 (60) being aware that it is effective in removing plaque Gr. 3= 40.1 (61) p=0,000. Conclusion Lack of interest of dentists from the methods of primary and secondary prevention of major oro-dental diseases is on absence of a dental prevention national program that to stimulate the attachment of specialists in prevention. Acknowledgements: This research was supported by the European project "Ergonomics, prevention and performing management in dental medicine by adopting European standards. Contract: POSDRU/81/3.2/S/55651, 2010-2013 - Project founded by European Social Fond Invest in People"